2014
DOI: 10.1097/mou.0000000000000116
|View full text |Cite
|
Sign up to set email alerts
|

Management of the incontinent patient with a sphincteric stricture following radical prostatectomy

Abstract: Management of the incontinent patient with concomitant BNC represents a challenging situation for the urologist. Several techniques are available to stabilize the BNC before safely proceeding with surgery for urinary incontinence. For the rare, complex case that has failed endoscopic management, referral to a surgeon experienced in reconstructive techniques is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…Additionally, four patients (7 %) experienced serious adverse events related to MMC instillation (osteitis pubis, rectourethral fistula with bladder floor necrosis, extensive necrosis of the bladder floor/trigone and pain) [23••]. This reinforces the previous concerns expressed by Cox and Herschorn about the risk of serious adverse events associated with adjuvant MMC injections [24].…”
Section: Endourologic Treatmentsupporting
confidence: 76%
“…Additionally, four patients (7 %) experienced serious adverse events related to MMC instillation (osteitis pubis, rectourethral fistula with bladder floor necrosis, extensive necrosis of the bladder floor/trigone and pain) [23••]. This reinforces the previous concerns expressed by Cox and Herschorn about the risk of serious adverse events associated with adjuvant MMC injections [24].…”
Section: Endourologic Treatmentsupporting
confidence: 76%
“…Literature regarding treatment of male SUI and concomitant bladder neck stricture is currently limited to small case series [14]. Anger et al [15] reported general feasibility of simultaneous stricture incision and AUS implantation without stating the detailed functional outcomes after the implantations.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are few data to support this claim; the results of a randomized controlled trial only showed that postoperative incontinence symptoms after RP were significantly improved by preoperative biofeedback combined with postoperative pelvic floor muscle training ( 17 ). The main indications for surgical treatment are patients whose urinary control is still not restored 1 year after RP, and surgical procedures include artificial urethral sphincter implantation, ball cavernous suspension, and transurethral injection of fillers ( 18 20 ). However, since post-operative RP patients may suffer from erectile dysfunction and retrograde ejaculation symptoms after surgery, which can affect the quality of life and psychological health of patients.…”
Section: Discussionmentioning
confidence: 99%